2008
DOI: 10.1007/s11187-007-9094-6
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive capacity and R&D tax policy: Are in-house and external contract R&D substitutes or complements?

Abstract: R&D, Absorptive capacity, Tax credit, R&D substitution, Technology policy, O31, O38, L26, L65, L86,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
(28 reference statements)
6
15
0
Order By: Relevance
“…It may generate negative consequences for the firms' core technological competences and the firms may actually lose their long-term competitive advantage (Sen and Rubenstein 1989;Quinn 1992). This substitutive relationship between external sourcing and internal R&D has been confirmed by a number of previous empirical studies (Blonigen and Taylor 2000;Higgins and Rodriguez 2006;Laursen and Salter 2006;Watkins and Paff 2009). Therefore, external technology acquisition should be considered as a double-edged sword.…”
Section: Introductionsupporting
confidence: 59%
“…It may generate negative consequences for the firms' core technological competences and the firms may actually lose their long-term competitive advantage (Sen and Rubenstein 1989;Quinn 1992). This substitutive relationship between external sourcing and internal R&D has been confirmed by a number of previous empirical studies (Blonigen and Taylor 2000;Higgins and Rodriguez 2006;Laursen and Salter 2006;Watkins and Paff 2009). Therefore, external technology acquisition should be considered as a double-edged sword.…”
Section: Introductionsupporting
confidence: 59%
“…They also found that both types of R&D are complementary in firms from high technology sectors and substitutes in low intensity technology sectors. Arora and Gambardella's (1990;1994) conclusions for the biotechnology sector coincide with those of Audretsch et al (1996) and other empirical works (Watkins and Paff, 2009) in pointing out that complementarities between internal and external R&D take place specially in the sectors characterized by a complex and fast technological change. In these ternal acquisition of technology raise as alternative to those firms financially constrained.…”
Section: Introductionsupporting
confidence: 81%
“…Second motivation examines if make-or-buy decision is relevant in terms of firm's performance; this view is concerned to explore the relationship between firms' innovation or economic results and the use of internal or external source of knowledge (Bönte, 2003;Frenz and Ietto-Gillies, 2009;Leiblein, Reuer and Dalsace, 2002;Montoya, Zárate and Martín, 2007;Vega-Jurado et al, 2008). Lastly, third point of interest analyzes complementarities between internal and external R&D activities; that is, if the productivity of the firm increases carrying out simultaneously both types of activities or, on the contrary, are substitutes Gambardella, 1990, 1994;Becker and Dietz, 2004;Caloghirou, Kastelli and Tsakanikas, 2004;Cassiman and Veugelers, 2006;Cohen and Levinthal, 1989;Schmiedeberg, 2008;Watkins and Paff, 2009) From this evidence, one can deduce the convenience of analyzing R&D expenditure as a concept of heterogeneous composition, which, both at the decision level and for its implications in firms' performance, could raise differences associated with the R&D combinations. Consequently, innovation strategy examined through the combination of internal and external R&D activities should be included in order to consider these heterogeneities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent research, however, suggest that alliance strategy, including technology alliance, has a negative effect on internal R&D capability (Higgins & Rodriguez, ; Laursen & Salter, ; Watkins & Paff, ). The reasons for negative relationships forming between technology alliance and internal R&D capability are as follows.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%